Information analytics: influence of crucial data pre-processing phases - Md Ajis, Ahmad Fuzi; Kamarudin, Nurfaizah; Baharin, Siti Hajar; Dahari, Siti Nur Shahira (Universiti Teknologi MARA, Johor, 2025)
Information analytics is one crucial process in any organization on obtaining insights based on existing data to facilitate data-driven decision making (Koukaras & Tjortjis, 2025). While data and information were crucially influencing the sustainability of organisations' operations and productivity, the whole process of data would so much rely on how such data is being processed (Martins et al., 2025). However, while many look towards the information or data processing, the pre-processing stage influences the quality of data to be prepared for the actual data processing phase (Lopez Miguel, 2021).